1983
DOI: 10.1063/1.331976
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ternary additions and precipitation on the critical current density and other superconducting properties in Nb-65 wt. %Ti

Abstract: The superconducting behavior of Nb-65 wt. %Ti and their ternary alloys with 1 wt. % Mo, Re, Si, Ta, V, and Zr was studied with regard to precipitation. Transmission electron microscopy studies were carried out to determine the size and distribution of the precipitates. In contrast to the commerical Nb-Ti superconductor the alloys show a quadratic dependence of the pinning force on the field close to the upper critical field. With a suitable precipitate size distribution but without workhardening these alloys d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Cold drawing in NbTi wires creates dislocations. Panek et al [19] and Matsushita and Kupfer [20] demonstrated that dislocations form high-field pinning centers.…”
Section: Physical Properties and Pinning Centers In Nbti Wiresmentioning
confidence: 99%
See 1 more Smart Citation
“…Cold drawing in NbTi wires creates dislocations. Panek et al [19] and Matsushita and Kupfer [20] demonstrated that dislocations form high-field pinning centers.…”
Section: Physical Properties and Pinning Centers In Nbti Wiresmentioning
confidence: 99%
“…Livingston [2] indicates that there are different types of pinning centers volume, surface, and point centers (e.g., precipitates and voids close to the coherence length). These pinning centers are most effective for increasing critical current density in low and medium magnetic fields [18][19][20]. In addition, Gajda et al [21] showed that these pinning centers in MgB 2 increase the critical current density (J c ) above 30 K, whereas pinning centers created by dislocations (line pinning centers) [2], substitution of C for B (lattice substitution pinning centers) [22], and precipitates inside the grain (inside grains pinning centers) [23] very effectively increase the J c in high magnetic fields [18].…”
Section: Introductionmentioning
confidence: 99%
“…The results presented in articles [8][9][10][11] suggest that high annealing pressure can improve the microstructure of MgB 2 material, reduce its void size, improve connections between the grains, allow smaller grains to be obtained and introduce strain-dislocations. In papers [12,13], the authors suggest that the dislocations create a line pinning center, which increases J c in high magnetic fields. The author in [14] suggests that the point pinning center can create not only intergranular precipitation but also voids similar in size to the coherence length; both are effective in pinning flux.…”
Section: Introductionmentioning
confidence: 99%
“…Identifying pinning centers and pinning mechanisms is of major importance for achieving higher critical currents in superconducting wires. In the early 1980s several flux line pinning (FLP) studies were made on the Nb-Ti system, considering the pinning produced by grain boundaries and small precipitates [1,2]. At that time, the defect microstructure of the optimized Nb-Ti conventional wires was often thought of as too complex for basic FLP studies.…”
Section: Introductionmentioning
confidence: 99%